Kontribusi Sukuk Negara terhadap Pembiayaan Pembangunan Berkelanjutan - Nurkaromah, Silvia Ripa; Marpudin, Fasya Dhiyaulhaq; Fadillah, Faiz Zaki; Adiansyah, Abdhi; Suryanto, Asep (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aims to analyse the contribution of State Sukuk (SBSN) to the financing of sustainable development in Indonesia within the framework of the Sustainable Development Goals. The study employs a qualitative approach through a literature review and content analysis of academic literature and official government reports. The results of the study indicate that State Sukuk, as stipulated in Law No. 19 of 2008 on SBSN, has become a strategic instrument in financing the State Budget. Through the Project-Based Sukuk scheme, funds are allocated to tangible assets and real projects such as educational infrastructure, transport, and public facilities that support the achievement of the SDGs, particularly SDG 4, SDG 7, and SDG 13. The issuance of Green Sukuk since 2018 has further strengthened the commitment to a green economy and low-carbon development. Furthermore, from an economic perspective, State Sukuk contribute to capital formation and the expansion of the investor base, whilst socially they improve access to basic services and promote equitable development. The implications of this research suggest that strengthening regulations, governance and Islamic financial literacy is necessary to optimise the use of Government Sukuk as an instrument of sustainable development in Indonesia.